Field‐Effect Transistors: Ultrathin MXene‐Micropattern‐Based Field‐Effect Transistor for Probing Neural Activity (Adv. Mater. 17/2016). Issue 17 (May 2016) - Xu, Bingzhe; Zhu, Minshen; Zhang, Wencong; Zhen, Xu; Pei, Zengxia; Xue, Qi; Zhi, Chunyi; Shi, Peng
Abstract : A field‐effect transistor (FET) based on ultrathin Ti3 C2 –MXene micropatterns is developed by C. Zhi, P. Shi, and co‐workers, as described on page 3333. The FET can be utilized for label‐free probing of small molecules in typical biological environments, e.g., for fast detection of action potentials in primary neurons. This device is produced with a microcontact printing technique, harnessing the unique advantages for easy fabrication.